INTERACTIVE MULTIMEDIA BASED ON EDUCATIONAL MAZE GAMES FOR THE TOPIC: STRUCTURE AND NOMENCLATURE OF HYDROCARBON COMPOUNDS - Suari, Merija; Mahartika, Ira; Octarya, Zona; Miterianifa (Yayasan Amanah Nur Aman, 2025)
Hydrocarbon compounds are compounds consisting of carbon (C) and hydrogen (H) atoms. In this material, students are required to understand the structure and nomenclature of hydrocarbon compounds. Thus, this material can also be made into an interesting learning tool if interactive multimedia based on educational maze games is used. Interactive educational games are one type of interactive educational media for training skills and teaching and learning activities for children. The purpose of this study is to determine the validity and practicality of learning media in the form of interactive multimedia based on educational maze games on the material of the structure and naming of hydrocarbon compounds. The type of research used is the DDR (Design and Development Research) development model with the stages of analysis, design, development, and evaluation. The overall validity obtained from several subject matter, media, and language experts was 92%, categorized as highly valid. The practicality results from the teacher response test were 85%, categorized as highly practical, and the student response test results were 93%, categorized as highly practical. Thus, this interactive multimedia learning media based on educational maze games is suitable for use and provides an innovative and interesting addition to learning media.